Redefining the timing and circumstances of the chicken's introduction to Europe and north-west Africa. (August 2022) - Best, Julia; Doherty, Sean; Armit, Ian; Boev, Zlatozar; Büster, Lindsey; Cunliffe, Barry; Foster, Alison; Frimet, Ben; Hamilton-Dyer, Sheila; Higham, Tom; Lebrasseur, Ophélie; Miller, Holly; et al.
Abstract: Abstract : Little is known about the early history of the chicken ( Gallus gallus domesticus ), including the timing and circumstances of its introduction into new cultural environments. To evaluate its spatio-temporal spread across Eurasia and north-west Africa, the authors radiocarbon dated 23 chicken bones from presumed early contexts. Three-quarters returned dates later than those suggested by stratigraphy, indicating the importance of direct dating. The results indicate that chickens did not arrive in Europe until the first millennium BC. Moreover, a consistent time-lag between the introduction of chickens and their consumption by humans suggests that these animals were initially regarded as exotica and only several centuries later recognised as a source of 'food'.